Imaging characteristics of diffuse large cell extra nodal non-Hodgkin's lymphoma involving the palate and maxillary sinus: a case report - Nadendla, Lakshmi Kavitha (Korean Academy of Oral and Maxillofacial Radiology, 2012)
Non-Hodgkin's lymphomas are a group of highly diverse malignancies and have a strong tendency to affect organs and tissues that do not ordinarily contain lymphoid cells. Primary extra nodal lymphoma of the hard palate is rare. Here, we present a case of diffuse large B cell lymphoma in a 60-year-old male patient that manifested as slightly painful ulcerated growth on the edentulous right maxillary alveolar ridge extending onto the palate, closely resembling carcinoma of the alveolar ridge. Computed tomography images showed the involvement of the maxillary sinus and right nasal cavity, along with destruction of hard palate, superiorly extending into the orbit. This case report highlights the importance of imaging to evaluate the exact extent of such large malignant lesions, which is essential for treatment planning.